Draft Annual Plan Vol. 2 2006-07 Karnataka - Planning Commission (Planning Commission, 2005)
Special Component Plan for Scheduled Castes (SCP)-I Draft Annual Plan 2006-07 - Financial Outlays : Proposals for SCP Draft Annual Plan 2006-07 Proposed Outlays - Outlay by Major Heads of De\ cloj 1 Bharath Nirman Programmes Draft Annual Plan (2006-07) Outlay by Heads of Developments for District Plans Centrallay Sponsored Scheme A Draft Annual Plan (2006-07) - Financial Outlays for TSP Draft Annual Plan (2006-07) - Physical Targets for TSP Draft Annual Plan (2006-07) - Financial Outlays for SCP for Scheduled Castes Draft Annual Plan (2006-07) - Physical Targets for SCP
Planning and Statistics Department